KERAWANAN LONGSOR LERENG JALAN STUDI KASUS RUAS JALAN SUKASADA – CANDI KUNING - Hartini, Ririn; Redana, I W.; Wardana, I.G.N. (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014, 2014)
Slope stability analysis along roads Denpasar – Singaraja have been calculated using Felenius Method and Software Plaxis 8.2. This calculation was conducted using  material model Mohr - Columb, soil cohesion (c) and tan f soil parameters. Calculations safety factor using phi – c reduction value, condition until structural failure occurs. The results of computation Felenius Method give stability value Fs < 1.5 which mean landslide would be accurred in this slope. Calculation using Plaxis 8.2 produce Fs > 1,5. This study has been on optimization of soil parameters, so that plaxis gives better result. This study may conclude that plaxis should be used with caution and with proper soil parameters
Keywords: Slope Stability, Felenius Method, Calculation using Plaxis 8.2.